[4 + 2]-Cycloadditions of a thiazol-based tricyclic 1, 4-diphosphinine and a new easy 1, 4-diphosphinine protection deprotection strategy. Issue 36 (4th September 2020) - Begum, Imtiaz; Kalisch, Tim; Schnakenburg, Gregor; Kelemen, Zsolt; Nyulászi, László; Streubel, Rainer
Abstract : Diels–Alder-reactions of a thiazol-2-thione-based, tricyclic 1, 4-diphosphinine were investigated, showing that the central aromatic π-system can react with various dienophiles. In one case, photochemical deprotection of the 1, 4-diphosphinine was found. Abstract : Diels–Alder-reactions of a thiazol-2-thione-based, tricyclic 1, 4-di-phosphinine were investigated, showing that the central aromatic π-system can react with various dienophiles. The reaction with 4-phenyl-1, 2, 4-triazoline-3, 5-dione was special as the product revealed a remarkable sensitivity towards light, thus enabling the photochemical deprotection of the tricyclic 1, 4-diphosphinine.